Process to better involve men in social and behavioural change communication in Rwanda - CGIAR Research Program on Livestock (2021)
Intervention Implementation completed and endline Knowledge, Attitudes and Practice (KAP) surveys conducted. Men were involved in the social and behavioural change communication on nutrition and animal source food consumption. Previous nutrition interventions focused on women.